Functional divergence within the APETALA3/PISTILLATA floral homeotic gene lineages - Lamb, Rebecca S. (National Academy of Sciences, 2003)
Changes in homeotic gene expression patterns or in the functions of the encoded proteins are thought to play a prominent role in the evolution of new morphologies. The floral homeotic APETALA3 (AP3) and PISTILLATA (PI) genes encode MADS domain-containing transcription factors required to specify petal and stamen identities in Arabidopsis. We have previously shown that perianth expression of AP3 and PI homologs varies in different groups of angiosperms with diverse floral structures, suggesting that changes in expression may contribute to changing morphology. We have investigated the possibility that changes in the functions of the encoded gene products may also have played a role in the evolution of different floral morphologies. AP3 and PI are members of paralogous gene lineages and share extensive similarity along the length of the protein products. Genes within these lineages encode products with characteristic C-terminal motifs that we show are critical for functional specificity. In particular, the C terminus of AP3 is sufficient to confer AP3 functionality on the heterologous PI protein. Furthermore, we have shown that the evolution of the divergent AP3 C-terminal domain in the core eudicots is correlated with the acquisition of a role in specifying perianth structures. These results suggest that divergence in these sequence motifs has contributed to the evolution of distinct functions for these floral homeotic gene products.